Respuestas
Respuesta dada por:
1
Comprobación de la primera ecuación
(2+5+2) x 3 =
- 2 - 3
(9) x 3 = 32 - 2 - 3
27 = 27
Comprobación de la segunda ecuación
(2+5+2) x 3 = 32 -![\sqrt{ 5^{2} } \sqrt{ 5^{2} }](https://tex.z-dn.net/?f=+%5Csqrt%7B+5%5E%7B2%7D+%7D+)
9 x 3 = 32 - 5
27 = 27
(2+5+2) x 3 =
(9) x 3 = 32 - 2 - 3
27 = 27
Comprobación de la segunda ecuación
(2+5+2) x 3 = 32 -
9 x 3 = 32 - 5
27 = 27
klewin2001:
muchas gracias
Preguntas similares
hace 7 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años